Digital creativity-based professional learning communities’ model to encourage differentiated learning design skills in elementary school teacher - Rintayati, Peduk; Syawaludin, Ahmad; Sunarno, Widha (Edelweiss Applied Science and Technology, 2024)
The professional practice of Learning Communities (PLC) demonstrates ineffectiveness when collaborative work hinders innovation in understanding individual student needs. This study aims to describe design of digital creativity-based PLC models for teachers to support the skills of developing differentiated learning in elementary school. The research used the Borg & Gall development design. The research subjects consisted of 180 elementary school teachers who had at least five years of teaching experience. The research data were obtained through questionnaires and documentation. Research data analysis was carried out with an interactive model. The results show that the findings of the needs analysis show that teachers need software to implement PLC. Products in the form of PLCs can be accessed via the website. Prototype of application PLC model based on digital creativity has four main menus consisting of the “KKG Team”, “Training”, “Work Space”, and “News” menus. The digital creativity-based PLC model was developed by producing an output in the form of an application that can be accessed via the website. The prototype model has not been validated by experts, so further studies are expected to be able to test the validity of the model and conduct field trials.